Gender, Violence, and Human Security : Critical Feminist Perspectives - Ewig, Christina; Ferree, Myra Marx; Tripp, Aili Mari (Book collections on Project MUSE., 2013)
The nature of human security is changing globally: interstate conflict and even intrastate conflict may be diminishing worldwide, yet threats to individuals and communities persist. Large-scale violence by formal and informal armed forces intersects with interpersonal and domestic forms of violence in mutually reinforcing ways. Gender, Violence, and Human Security takes a critical look at notions of human security and violence through a feminist lens, drawing on both theoretical perspectives and empirical examinations through case studies from a variety of contexts around the globe. This fas.